Influence of religious philosophy on parental school choice: A qualitative analysis - Salman, Ibnu; Safaria; Anwar, Sumarsih; Habibullah, Achmad; Siswanto, Heni Waluyo (Kasetsart Journal of Social Sciences, 2026)
In this paper, attention is paid to the extent to which religious philosophy can determine parental choice of a school for their children. It has become common in families to look for an institution that shares their beliefs, thus it is worth knowing the reasons behind such choices. The goal of this study is to understand the key objectives of parents who put such priorities above other factors when choosing a school. More specifically, library research and a phenomenological approach formed the qualitative research design data sources which were various articles and books. The results show that parents consider the focus on the religious education of their children, the similarity of beliefs in the family and the school, and the possibility of belonging to a faith community in a school as the main criteria for the selection of schools. These are important areas in the nurturing of children’s morals and ethics. From the findings of the study, it can also be stated that such parents conform to the school’s existing philosophy which appeals to them. There has been an attempt in this research paper that suggests that these schools should develop programs that will cultivate their students’ religious beliefs holistically. This program will also be useful to families whose philosophical views have been extended to educational institutions that are highly confessional.